Tourism Policy and Enabling Conditions; A Comparative Analysis Related to Mediterranean Destinations - Goral, Ramazan (European Journal of Multidisciplinary Studies, 2016)
On the study, competitive position of eight destinations on Mediterranean Basin (Turkey, Greece, Italy, France, Spain, Egypt , Tunisia and Morocco ) related to Tourism Pol?cy and Enabling Conditions were analyzed as comparative in terms of both index wide and also sub-factors as Data of Travel and Tourism Competition Index (TTCI) which was published by World Economic Forum in 2015 was used. According to analysis ' s findings, most competitive first three destinations are respectively Spain, Greece and Tunisia in terms of general index of Tourism Pol?cy and Enabling Conditions. Destinations' cImpetitive positions' order changes in terms of sub-factors. Five point likert scale was used to make meaningful country's competitive position by points that it got from criteria belonging to countries' sub-factors. Accordingly, the following points which countries got from criteria express competitive positions: 5= Very well, 4=Well, 3=Medium, 2=Bad ,1=Very bad. Moreover, when eight destinations on Mediterranean Basin are evaluated, there is a significant relation between Tourism Pol?cy and Enabling Conditions and Tourism Income and Number of Tourist in terms of statistics.
Keywords: Tourism Polıcy and Enabling Conditions, Prioritization of Travel, International Openness, Price Competition, Environmental Sustainability